Sharpen Listening Skills Through Innovative Probing-Promting Application of Cake in Limited Face-to-Face Learning in the Era of Independent Learning - Sugandi, Bastian; Syafiq, Ahmad (Institut Agama Islam Negeri (IAIN) Curup, 2023)
The objective of this research is to find out the effectiveness of the application cake in order to increase the students listening comprehension easy and fun. The student also easy understands. There are two stages method of research they are: First, the researcher conducts a literature review, problem analysis, and observation, determines the sample, surveys on vocabulary comprehension, and pre-tests to determine the abilities of the research subjects, and the second is carried out by implementing the learning method which is then analyzed so that it leads to the final instrument test, then the last is the researcher conducted a post-test. Meanwhile the instrument in this research is pretest and posttest. The sample of this research is members of the English Club at the University of Muhammadiyah Lampung. The number of samples taken was 39 students. The instruments to be used are pre-test and post-test. The results of the pot test showed as many as 3 respondents got scores with a range between 40-50.Â A total of 7 respondents scored between 52-60, then dial with 7 respondents who got a score between 62-70. The highest score is dominated by the 4th series with 18 respondents who get scores with a range between 72-80. Closed with 4 people who got a score between 82-90. The use of cake application in the listening learning process has quite a significant impact on learning achievement, when compared to the previous score, the post-test score is higher than the pre-test score.